Standardisasi Simplisia dan Ekstrak Etanol Daun Leilem (Clerodendrum minahassae Teisjm. & Binn.) - Yuri Pratiwi Utami; Abdul Halim Umar; Reny Syahruni; Indah Kadullah (STIFA Makassar, 2017)
The leaves of Clerodendrum minahassae Teijsm. & Binn. hasmany pharmacologica leffects as traditional medicine. Rawmaterialof traditional medicine should be standardized. Standardization of simplicia and ethanolic extract of C. minahassae leaves was performed to determine the standard parameters both of simplicia and extract. Determination ofquality standard extract include specific and non-specific parameters.The extract of C. minahassae obtained by maceration from C. minahassae leaves (C. minahassae folium) using ethanol with the acquisitionofrendement about 22%. The macroscopic obsevations showed that simplicia of C. minahassae leaves is greenish brown, egg-shaped, sharp edges, blunt stem, slippery surface, flat-brimmed, generally there are six pairs of pinnate bone leaves, the average leghth is 11,1 cm and the average width is 5,3 cm.The organoleptic of ethanolic extract is thick, brownish-black, has the distinctive smell and tastes bitter. Fragment identifiers of C. minahassae leaves such as crystalline calcium oxalate with stiloid shaped, file vessels with thickening ring, hair coverings conical and has a hair tip pointy, stomata with stone cell, the upper epidermis with stomata anomocytic types and lower epidermis with irregularly polygonal. Content of water-soluble compounds of simplicia is 19,932% and 52,096% of extract, while the content of ethanol-soluble compounds of simplicia is 11,776% and 35,108% of extract. The extract contains alkaloids, steroids, flavonoids and tannins​. Simplicia and extract, each containing ≤ 10% of water. Total ash content of simplicia is 27,783% and 12% of extract, while the acid insoluble ash content of simplicia is 4,242% and 2,518% of extract. The loss of drying of simplicia is 12,399% and 24,603% of extract. The density of extract is 1,055 g/ml. Total bacterial and fungal contamination of extract are qualified, with the values are 5.4 x 102 colonies/g and 5.0 x 102 colonies/g respectively.